2020
DOI: 10.17718/tojde.849907
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Language Learner Autonomy Through Interdependence: The Power of Wikis

Abstract: The present study reports on a collaborative writing project initiated and completed by 18 Iranian English language learners enrolled in an online writing course. Using a wiki as the core element of the project, the aim of the course was fostering learner autonomy in online settings based on the collaborative autonomous language learning framework proposed by Kessler and Bikowski (2010). The outcome of collaborative writing project was a text created in a wiki, which was manually analyzed from the very beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Personal construct theory [53] embraces the notion of self-concept, and it is deemed to have a twofold relation with autonomy while they both support the promotion of each other [54,55]. us, the predicting power of ASC with respect to its subcomponents (academic confidence and effort) portrayed that academic confidence correlated more strongly with LA in writing than did academic effort.…”
Section: Discussionmentioning
confidence: 99%
“…Personal construct theory [53] embraces the notion of self-concept, and it is deemed to have a twofold relation with autonomy while they both support the promotion of each other [54,55]. us, the predicting power of ASC with respect to its subcomponents (academic confidence and effort) portrayed that academic confidence correlated more strongly with LA in writing than did academic effort.…”
Section: Discussionmentioning
confidence: 99%
“…As asserted by Sistyawan et al (2022), teachers are not purely conveyors of information; they are facilitators who guide students through the language learning process. This involves not only delivering lessons but also engaging in interactive and student-centered teaching methodologies (Emiliasari, Prasetyo, & Syarifah, 2019;Almubarokah & Arifani, 2021;Sadaghian & Marandi, 2021). In addition, the evolving nature of technology in education has also redefined the teacher's role.…”
Section: Definitions Of the Concept 'Teacher Role'mentioning
confidence: 99%
“…It included content training, choosing activities, online activities, and utilizing ICT tools. Studies in Iranian and Indonesian university contexts have revealed that the technology tools helped encourage learners to be autonomous with support from the teacher to guide learners to various materials and psychosocial encouragement to motivate learners simultaneously (Sadaghian & Marandi, 2021;Yusnimar, 2019). Therefore, autonomous learning enhanced students' performance in listening and speaking, increased students' learning outcomes in reading and writing, and received positive feedback from the EFL learners (Choi & Lee, 2020;Pratiwi et al, 2016;Zulaihah & Harida, 2017).…”
Section: Autonomous Learningmentioning
confidence: 99%
“…(Ahmed et al, 2020;. Furthermore, digital technology is viewed as one of the most powerful tools to promote autonomous learning as it supports teachers to be the facilitator in class (Ling et al, 2020;Sadaghian & Marandi, 2021). Learners should take responsibility for their learning, take an active role in the learning context and methods, and evaluate their progress (Choi & Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%